Laboratory practices for manual blood film review: Results of an IQMH patterns of practice survey. (17th September 2020) - Leung, Elaine; Johnston, Anna; Olsen, Brian; Chang, Hong; Martin, Tracy; Wozniak, Miranda; Good, David
Abstract: Introduction: Examination of a blood film is the second most common hematology test, after the complete blood count. Interpretation of a peripheral blood film by trained laboratory professionals provides valuable diagnostic information. The Institute for Quality Management in Healthcare (IQMH) Hematology Scientific Committee developed a questionnaire to gather information regarding current practices for manual blood film review and reporting from laboratories participating in IQMH Morphology proficiency testing (PT) surveys. Methods: An online survey was distributed to 174 laboratories, 97% submitted results. Results: Of the respondents, the majority (82%) indicated affiliation with small‐ or medium‐sized hospitals (<500 beds). 80% of respondents had core laboratory technologists performing manual blood film reviews, while only 2% utilized dedicated hematology technologists with morphology expertise. All respondents had a policy for manual blood film review by a technologist, 70% did not have blood films reviewed by a senior/charge technologist prior to review by a physician. The majority (88%) of participants included morphological findings in their critical result list; of these, 98% include malaria and 88% include the first‐time finding of blasts as critical results. 59% of participants indicated that they have a procedure in place to ensure that interpretation and confirmation of first‐time potentially significant morphological findings are available from a physician at all times. Conclusion: This survey identified significant variation in blood film review and reporting practices across participating laboratories. The IQMH Hematology Scientific Committee will develop best practice recommendations to guide and standardize practice.